Skeletal muscle pathways of contraction-enhanced glucose uptake - Santos, J. M.; Ribeiro, S. B.; Gaya, A. R.; Appell, H. J.; Duarte, J. A. (International Journal of Sports Medicine, 2008)
Muscle contraction acutely increases glucose transport in both healthy and type 2 diabetic individuals. Since glucose uptake during muscle contraction has been observed in the absence of insulin, the existence of an insulin-independent pathway has been suggested to explain this phenomenon. However, the exact mechanism behind the translocation of GLUT4 vesicles through the sarcolemma during muscle contraction is still unknown. Some substances, such as AMPK and calcium activated proteins, have been suggested as potential mediators but the exact mechanisms of their involvement remain to be elucidated. A hypothetical convergence point between the insulin cascade and the potential pathways triggered by muscle contraction has been suggested. Therefore, the earliest concept that two different routes exist in skeletal muscle has been progressively modified to the notion that glucose uptake is induced by muscle contraction via components of the insulin pathway. With further consideration, increased glucose uptake and enhanced insulin sensitivity observed during/after exercise might be explained by a metabolic- and calcium-dependent activation of several intermediate molecules of the insulin cascade. This paper aimed to review the literature in order to examine in detail these concepts behind muscle contraction-induced glucose uptake.